Review of Pioneer Hungarian Women in Science and Education - Hegyi, Pál (AMERICANA E-journal of American Studies in Hungary, 2023)
Pioneer Hungarian Women in Science and Education Réka M. Cristian and Anna Kérchy (Eds.) Akadémiai Kiadó, Budapest, 2022. 151 pp. ISBN: 978 963 454 771 6